Human Resource Development Strategy Using EFE, IFE, IE, and SWOT Matrices at Indonesian Baptist Theological Seminary - Karnawati Karnawati; Heri Yanto; Ida Zulaeha; Sungkowo Edi Mulyono (International Conference on Science, Education, and Technology, 2023)
Educational institutions need to be critical in making strategic plans for human resource development. If not, there is a possibility that the educational institution will experience a decline in quality which can result in the closure of the educational institution. This study aims to find reliable strategies in human resource development using EFE, IFE, IE, and SWOT matrices. The method used is a qualitative approach, with data collection techniques of interviews, observations, document studies, and FGDs. The results of the study can be concluded that Indonesian Baptist Theological Seminary is in quadrant I position which means that the institution is in a growing and developing situation, the institution has high strengths and opportunities to support development policies, while the internal position is on average, which means that it is still not responding to opportunities and threats. Then the strategies obtained through the SWOT matrix are: 1) SO strategy: need to recruit students from GGBI members; institutions need to actively send information to social media regarding SST Baptist Indonesia news as a massive promotion; establish cooperation to increase the capacity of staff and employees through further education and training. 2) WO strategy: report the needs of facilities and infrastructure to the foundation for follow-up; conduct training for staff in utilizing existing information systems; train staff and employees to collaborate with other STTs and other institutions.3) ST strategy: mobilize teaching staff to play a role in outreach to teenagers; create a business unit to increase the added value of the institution for the welfare of employees. 4) WT strategies: Evaluate staff performance and conduct follow-up; hold a meeting with GGBI (Association of Baptist Churches of Indonesia) to discuss staff issues and find solutions.